(untitled) (mathematica didactica, 2024)
This paper explores whether students connect their concept image with the concept definition in task assignments and reports on a study in which 26 university calculus students solve four exercises on convergence of sequences. In the process, different practices were identified that indicate such interplay. Practices do not refer to individual approaches, but to a more comprehensive set of activities shared by the research group. As a result of the research, the article focuses on a practice of connection concept image and concept definition that was particularly activated by the students: The interplay of conceptions, visual representations and the formal concept definition.